PEMBAKUAN INSTRUMEN CAREER WELLBEING BERBASIS LAMA BEKERJA, KUALIFIKASI PENDIDIKAN, DAN WILAYAH TEMPAT KERJA SERTA HUBUNGANNYA DENGAN KOMPETENSI PROFESIONAL GURU BK DI INDONESIA - M. Fiqri Syahril, - (2023)
Career wellbeing merupakan topik yang sangat perlu dimiliki bagi para pekerja atau profesi termasuk guru bimbingan dan konseling sebagai personil sekolah yang mewujudkan tercapainya tujuan pendidikan nasional dalam keterkaitannya dengan layanan bimbingan dan konseling. Pembakuan skala career wellbeing terhadap bidang keilmuan bimbingan dan konseling diharapkan dapat mengukur sejauh mana kepuasan, kesiapan, dan tujuan karier bagi bagi guru BK sebagai pendidik yang profesional. Penelitian bertujuan untuk melakukan pembakuan skala career wellbeing bagi guru bimbingan dan konseling di Indonesia dan mengetahui pengaruh career wellbeing terhadap kompetensi profesional guru bimbingan dan konseling. Pendekatan yang digunakan dalam penelitian yaitu pendekatan kuantitatif. Sampel penelitian ialah 1000 orang guru bimbingan dan konseling di Indonesia. Teknik pengumpulan data menggunakan skala career wellbeing guru bimbingan dan konseling. Hasil penelitian diperoleh skala career wellbeing guru BK yang telah dibakukan dalam konteks Indonesia serta terdapat pengaruh career wellbeing terhadap kompetensi profesional guru bimbingan dan konseling. Career welfare is a topic that really needs to be owned by workers or professions including guidance and counseling teachers as school personnel who realize the achievement of national education goals in relation to guidance and counseling services. It is expected that the standardization of the career welfare scale in the scientific field of guidance and counseling can measure the extent of satisfaction, readiness, and career goals for guidance amd counseling teachers as professional educators. The aim of the study was to standardize the career welfare scale for guidance and counseling teachers in Indonesia and to determine the effect of career welfare on the competence of professional guidance and counseling teachers. The approach used in this research is a quantitative approach. The research sample is 1000 guidance and counseling teachers in Indonesia. The data collection technique uses guidance and counseling teacher on career scale welfare. The results of the study obtained a career scale for guidance and counseling teachers' welfare which has been standardized in the Indonesian context and there is an influence of career welfare on the competence of guidance and counseling professional teachers. The use of standard measuring instruments to support assistants can then directly use measuring tools for career welfare guidance and counseling teacher.